2019
DOI: 10.1101/746214
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nf1deletion results in depletion of theLhx6transcription factor and a specific loss of parvalbumin+ cortical interneurons

Abstract: Neurofibromatosis-1 (NF-1) is a monogenic disorder caused by mutations in the NF1 gene, which encodes the protein, Neurofibromin, an inhibitor of Ras GTPase activity. While NF-1 is often characterized by café-au-lait skin spots and benign tumors, the mechanisms underlying cognitive changes in NF-1 are poorly understood. Cortical GABAergic interneurons (CINs) are implicated in NF-1 pathology but cellular and molecular changes to CINs are poorly understood. We deleted Nf1 from the medial ganglionic eminence (MGE… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 63 publications
1
14
0
Order By: Relevance
“…While the transcriptional mechanisms of CIN development have been intensely studied, the signaling pathways that serve as intermediaries between extracellular stimulation and gene expression changes are relatively less clear. Recent work has shown that hyperactive MEK-ERK1/2 and PI3K-linked signaling pathways have critical roles in CIN development and subtype specification (Angara et al, 2020; Malik et al, 2019; Vogt et al, 2015). However, the field still lacks crucial information on whether activation of ERK1/2 signaling is necessary for CIN subtype identity.…”
Section: Introductionmentioning
confidence: 99%
“…While the transcriptional mechanisms of CIN development have been intensely studied, the signaling pathways that serve as intermediaries between extracellular stimulation and gene expression changes are relatively less clear. Recent work has shown that hyperactive MEK-ERK1/2 and PI3K-linked signaling pathways have critical roles in CIN development and subtype specification (Angara et al, 2020; Malik et al, 2019; Vogt et al, 2015). However, the field still lacks crucial information on whether activation of ERK1/2 signaling is necessary for CIN subtype identity.…”
Section: Introductionmentioning
confidence: 99%
“…One possible explanation for the different situation in nf1 +/mice could be that the development of inhibitory innervation in BDNF transgenic mice (Huang et al, 1999b) and benzodiazepine-treated mice (Iwai et al, 2003) was also advanced, while this was not the case in nf1 +/mice. A recent study in mice in which nf1 was inactivated in precursors of cortical interneurons (Angara et al, 2020) showed evidence that nf1 deletion could even delay PV+ interneuron development. Fewer perineuronal nets were found in somatosensory cortex of these mice.…”
Section: Discussionmentioning
confidence: 99%
“…We performed MGE primary cultures as described in Angara et al ( 2020 ). Briefly, we cultured MGE cells in DMEM supplemented with 10% FBS and penicillin/streptomycin from time of seeding until 1 day in vitro .…”
Section: Methodsmentioning
confidence: 99%
“…CIN dysfunction is implicated in ASD and altered in both humans diagnosed with ASD and in ASD genetic deletion models (Vogt et al, 2015a , 2018 ; Hoffman et al, 2016 ; Hashemi et al, 2017 ; Jung et al, 2017 ; Soghomonian et al, 2017 ; Pla et al, 2018 ; Elbert et al, 2019 ; Malik et al, 2019 ; Angara et al, 2020 ). CINs are derived from the medial and caudal ganglionic eminences (MGE and CGE), as well as the preoptic area (Wonders and Anderson, 2006 ; Gelman et al, 2011 ; Hu et al, 2017b ).…”
Section: Introductionmentioning
confidence: 99%